Pharmacoepidemiological Basis of Antibacterial Drugs in Pneumonia outside the Hospital - Salokhitdinovna, Kadirova Shakhlo (Journal of Science in Medicine and Life, 2024)
The etiology of CAP is directly related to the normal microflora of the "non-sterile" parts of the upper respiratory tract (oral cavity, nose, oropharynx and nasopharynx). Of the many types of microorganisms that colonize the upper respiratory tract, only a few can cause an inflammatory reaction by penetrating the respiratory parts of the lungs, even with a minimal violation of protective mechanisms. Typical bacterial pathogens of SAP.